2009
DOI: 10.1111/j.1755-3768.2009.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic technique and anatomically imposed limitations of confocal scanning laser Doppler flowmetry at the optic nerve head level

Abstract: ABSTRACT.Many studies have suggested an association between blood flow dysregulation and glaucomatous damage to the optic nerve. Confocal scanning laser Doppler flowmetry (CSLDF) is a technique that measures the capillary blood flow of the retina and optic nerve head and provides a two-dimensional map of ocular perfusion in these areas. This review discusses the anatomy of the anterior optic nerve vasculature and the capabilities and limitations of the CSLDF. Methods to minimize error and to acquire more relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 78 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Previous studies demonstrated reduced ocular vascularization in glaucomatous eyes in the ophthalmic, retinal, choroidal, and retrobulbar circulation [2,3]. Many studies investigated the ocular blood flow using methods such as fluorescein angiography [4], Heidelberg retina flowmeter which combines the principles of scanning laser Doppler flowmetry and confocal scanning laser techniques [5], and color Doppler imaging [6]. However, the clinical application of these methods was limited by the invasiveness of some of them, the lack of quantitative measures and the inability to visualize the microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated reduced ocular vascularization in glaucomatous eyes in the ophthalmic, retinal, choroidal, and retrobulbar circulation [2,3]. Many studies investigated the ocular blood flow using methods such as fluorescein angiography [4], Heidelberg retina flowmeter which combines the principles of scanning laser Doppler flowmetry and confocal scanning laser techniques [5], and color Doppler imaging [6]. However, the clinical application of these methods was limited by the invasiveness of some of them, the lack of quantitative measures and the inability to visualize the microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…The artery branches into radial arterioles and smaller vessels on the vitreal surface of the retina. 2 Blood is returned through radial venules on the retinal surface that empty into the central retinal vein in the optic nerve. The total blood flow supplied to the choroid is much greater than that supplied to the retina.…”
Section: Anatomical Aspectsmentioning
confidence: 99%
“…The pial vessels obtain their supply either directly from the ophthalmic artery (OA) or indirectly from the recurrent branches from the SPCAs. 2 …”
Section: Anatomical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of this technique is that velocity and volume are measured in arbitrary units, making the comparison between CSLDF measurements and other technologies quite difficult. (54, 109) Nevertheless, CSLDF measurements could be used to compare relative changes in the ocular microcirculation occurring in patients at different stages of OAG progression with the predictions of mathematical models describing ocular hemodynamics; this comparison would help identify which structural, vascular and systemic factors would cause those changes.…”
Section: Techniques For Non-invasive Ocular Measurementsmentioning
confidence: 99%